THE FEASIBILITY OF HOSPITALITY BUSINESS INCESTMENTS IN BANJAR CITY - Caroline, Angela; Yaprimadi, Ivan Mulyadi (Fakultas Pendidikan Ekonomi dan Bisnis, 2018)
The Feasibility of Hospitality Business Investments in Banjar City. This study aims to help investors assess the feasibility of business hotels in the Banjar City. To assess the business feasibility of the hotel was used several frameworks to analyze environmental factors consisting of PEST Analysis, and Five Forces. Environmental analysis is reinforced by the financial analysis made based on interviews with investors and employees of PT.X which is a development company that wants to build a business hotel in the Banjar City. Financial analysis is made using the NPV, IRR, and Payback Period approaches. The results of these calculations are used to estimate the feasibility of business hotels in the city of Banjar. However, this study is limited to the condition of hotel competition in Banjar City nowadays and limited to the business plan of PT. X